"The biggest problem we've ever had to face": how families manage driving cessation with people with dementia. (14th September 2015) - Liddle, Jacki; Tan, Amelia; Liang, Phyllis; Bennett, Sally; Allen, Shelley; Lie, David C.; Pachana, Nancy A.
ABSTRACT: Background: It is recognized that people with dementia are likely to need to stop driving at some point following diagnosis. Driving cessation can lead to negative outcomes for people with dementia and their family caregivers (FC), who often experience family conflict and tension throughout the process. Family experiences surrounding driving cessation have begun to be explored but warrant further examination. Methods: Using a descriptive phenomenological approach, semi-structured interviews were undertaken with key stakeholders, including 5 retired drivers with dementia, 12 FC, and 15 health professionals (HP). Data were analyzed inductively to explore the needs and experiences of people with dementia and FC. Results: The data revealed a range of possible interactions between people with dementia and FC. These were organized into a continuum of family dynamics according to levels of collaboration and conflict: in it together, behind the scenes, active negotiations, and at odds . At the in it together end of the continuum, people with dementia and FC demonstrated collaborative approaches and minimal conflict in managing driving cessation. At the at odds end, they experienced open conflict and significant tension in their interactions. Contextual factors influencing family dynamics were identified, along with the need for individualized approaches to support. Conclusions: The continuum of family dynamics experienced during driving cessation may help clinicians better understand and respond to complex family needs. Interventions should be tailored to families' distinctive needs with consideration of their unique contextual factors influencing dynamics, to provide sensitive and responsive support for families managing driving cessation.